1 Public Records of the Colony of Connecticut 351 (J. Hammond Trumbull ed., 1850) (enacted 1646) - (:unkn) unknown (My University, 1660)
"This Court orders, that ifany Indians shal bring in Guns into any o fthe Townes in this Coll: It shal be lawful for any on eof ye English to seize on their guns, and to keep them until there be 10s. a piece brought to redeem each gun, wch shal be devided, one half to ye Treasurie, the other half to ye seazer."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES